Pengaruh Struktur Kepemilikan, Struktur Modal dan Tingkat Proofitabilitas terhadap Risk Management Disclosure - Raisa Tris Septia KN (AKT 16 UMY 037, 2016)
This research aimed to analyze the influence of the ownership structure, capital structure and profitability rate towards risk management disclosure. This research used secondary data from bank corporate that listed in Indonesia Stock Exchange in the period 2011-2014. This research used purposive sampling method and used double linier regression analysis tool. Before examining the regression, the data had been examined using classic asumption test first. The result of this research shows that capital structure have a positive influence towards risk management disclosure. On the other hand, manajerial ownership, public ownership, profitability rate have no an influence towards risk management disclosure. Keywords: risk management disclosure, manajerial ownership, public ownership, capital structure, profitability rate.